1893 Okla. Terr. Stat. 503, ch. 25, art. 45 § 3 - (:unkn) unknown (General Publisher, 1893)
Prohibited the sale or giving of any pistol, revolver, Bowie knife, dirk, dagger, slung-shot, sword cane, spear, metal knuckles, dirk knife, loaded cane, billy or any other kind of knife or instrument manufactured or sold for the purpose of defense, or other offensive or defensive weapon to a minor.
--
Keywords: TRANSFER - MINORS